The impact of sales promotion on consumer buying behaviour - Chiew, Tung Moi (2004)
Various sales promotional tools (promo-tools) have been employed by marketers over the years to generate sales for their offerings. The use of coupon, price discount, free sample, bonus pack, and in-store display are examples of sales promotion strategies adopted by organizations to generate product trial and repurchase. Although most of these tools are used very frequently in Malaysia, there is still very poor understanding of their impact on product trial and repurchase among researchers and practitioners who deploy these strategies. The current research is an attempt to unveil the influence of coupon, cash discount, free sample, bonus pack, and in-store display on product trial and repurchase among Malaysia consumers, especially consumers in Kata Kinabalu, Sabah. Randomly selected consumers in Kata Kinabalu, Sabah were surveyed using structured questionnaire. A total of 312 usable responses were received and analyzed. The results show that price discount, free sample, bonus pack, and in-store display are robust determinants of product trial. Coupon is not. And product trial acts as a mediator between sales promotional tools and repurchase. Details of the findings and their implications are discussed.